Stone Fruit as Biofactories of Phytochemicals With Potential Roles in Human Nutrition and Health - Lara, María Valeria; Bonghi, Claudio; Famiani, Franco; Vizzotto, Giannina; Walker, Robert P.; Drincovich, María Fabiana (Frontiers in Plant Science, 2020)
Phytochemicals or secondary metabolites present in fruit are key components contributing to sensory attributes like aroma, taste and color. In addition, these compounds improve human nutrition and health. Stone fruit are an important source of an array of secondary metabolites that may reduce the risk of different diseases. The first part of this review is dedicated to the description of the main secondary organic compounds found in plants which include (a) phenolic compounds, (b) terpenoids/isoprenoids and (c) nitrogen or sulfur containing compounds; and their principal biosynthetic pathways and their regulation in stone fruit. Then, the type and levels of bioactive compounds in different stone fruits of the Rosaceae family such as peach (Prunus persica), plum (P. domestica, P. salicina and P. cerasifera), sweet cherries (P. avium), almond kernels (P. dulcis, syn. P. amygdalus) and apricot (P. armeniaca); are presented. The last part of this review encompasses pre- and postharvest treatments affecting the phytochemical composition in stone fruit. Appropriate management of these factors during pre- and postharvest handling, along with further characterization of phytochemicals and the regulation of their synthesis in different cultivars, could help to increase the levels of these compounds, leading to the future improvement of stone fruit not only to enhance organoleptic characteristics but also for the benefit of human health.